Mercury fluxes through the sediment water interface and bioavailability of mercury in southern Baltic Sea sediments - Jacek Bełdowski; Michał Miotk; Janusz Pempkowiak (Oceanologia, 2009)
Sediment cores collected in several areas of the southern Baltic were analysed for total mercury (HgTOT) and five operationally defined mercury fractions: HgA - contained in pore waters, HgF - bound to fulvic acids, HgH - bound to humic acids, HgS - bound to sulphide, and HgR - residual. An effort was made to quantify mercury fluxes at the sediment/water interface in the study area. Net mercury input, calculated on the basis of sedimentation rate and concentration in the uppermost sediments, ranged from 1 to 5.5 ng cm-2 year-1. Mercury remobilisation from sediments due to diffusion and resuspension was calculated from the proportion of labile mercury and the velocity of near-bottom currents. The results showed that the return soluble and particulate fluxes of mercury from the sediments to the water column constitute a substantial proportion of the input (20-50%), and are slightly higher than those found in pristine areas, although they are less than the values recorded in areas with a history of mercury contamination. In addition, an index was developed to assess the methylation potential of mercury in sediments. Mercury contained in pore waters, and mercury bound to fulvic and humic acids together with Loss on Ignition were used to calculate the semi-quantitative methylation potential (Pm). Despite the simplicity of this approach, Pm correlates well with methyl mercury in fish from the study area.full, complete article (PDF - compatibile with Acrobat 4.0), 291.3 kB